2021
DOI: 10.1021/acs.orglett.1c00556
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative α-C–C Bond Cleavage of 2° and 3° Alcohols to Aromatic Acids with O2at Room Temperature via Iron Photocatalysis

Abstract: The selective α-C−C bond cleavage of unfunctionalized secondary (2°) and tertiary alcohols (3°) is essential for valorization of macromolecules and biopolymers. We developed a blue-light-driven iron catalysis for aerobic oxidation of 2°and 3°alcohols to acids via α-C−C bond cleavages at room temperature. The first example of oxygenation of the simple tertiary alcohols was reported. The iron catalyst and blue light play critical roles to enable the formation of highly reactive O radicals from alcohols and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 81 publications
0
22
0
Order By: Relevance
“…From the reaction condition studies and the UV/Vis spectra (Figure 4c and Figure S9), Fe III is believed to be the real photocatalyst, which can be oxidized from Fe II simply under oxygen atmosphere. Based on the above observations and the relevant mechanism studies reported, [28,43,51,[54][55][56][57][58] the proposed Table 3. Depolymerization of different polymers through oxidative CÀ C bond cleavage.…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…From the reaction condition studies and the UV/Vis spectra (Figure 4c and Figure S9), Fe III is believed to be the real photocatalyst, which can be oxidized from Fe II simply under oxygen atmosphere. Based on the above observations and the relevant mechanism studies reported, [28,43,51,[54][55][56][57][58] the proposed Table 3. Depolymerization of different polymers through oxidative CÀ C bond cleavage.…”
Section: Resultsmentioning
confidence: 85%
“…[24][25][26][27][28][29][30][31][32][33] In addition, CÀ C bond scission of alcohols and ketones through alkoxyl radical intermediates applying inexpensive catalysts were reported recently. [34][35][36][37][38][39][40][41][42][43] Despite limitations, these results illustrate the possibility of developing an economic system for oxidative CÀ C bond cleavage in an environmentally friendly way (Figure 1b). Specially, iron may be a good catalyst candidate, which can perform both CÀ H bond oxidation [25,26,28] and oxidative CÀ C bond cleavage [43] through photocatalysis.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Earth abundant metals were found to transform alkanes to alcohols and ketones under oxygen atmosphere [24][25][26][27][28][29][30][31][32][33] . In addition, C-C bond scission of alcohols and ketones through alkoxyl radical intermediates applying inexpensive catalysts were reported recently [34][35][36][37][38][39][40][41][42][43] . Though with limitations, these results illustrate us the possibility of developing an economic system for oxidative C-C bond cleavage in an environmentally friendly way (Fig.…”
mentioning
confidence: 99%